Major bleeding risk among non‐valvular atrial fibrillation patients initiated on apixaban, dabigatran, rivaroxaban or warfarin: a "real‐world" observational study in the United States. Issue 9 (23rd August 2016) - Lip, Gregory Y. H.; Pan, Xianying; Kamble, Shital; Kawabata, Hugh; Mardekian, Jack; Masseria, Cristina; Bruno, Amanda; Phatak, Hemant
Summary: Background: Limited data are available about the real‐world safety of non‐vitamin K antagonist oral anticoagulants (NOACs). Objectives: To compare the major bleeding risk among newly anticoagulated non‐valvular atrial fibrillation (NVAF) patients initiating apixaban, warfarin, dabigatran or rivaroxaban in the United States. Methods and results: A retrospective cohort study was conducted to compare the major bleeding risk among newly anticoagulated NVAF patients initiating warfarin, apixaban, dabigatran or rivaroxaban. The study used the Truven MarketScan ® Commercial & Medicare supplemental US database from 1 January 2013 through 31 December 2013. Major bleeding was defined as bleeding requiring hospitalisation. Cox model estimated hazard ratios (HRs) of major bleeding were adjusted for age, gender, baseline comorbidities and co‐medications. Among 29 338 newly anticoagulated NVAF patients, 2402 (8.19%) were on apixaban; 4173 (14.22%) on dabigatran; 10 050 (34.26%) on rivaroxaban; and 12 713 (43.33%) on warfarin. After adjusting for baseline characteristics, initiation on warfarin [adjusted HR (aHR): 1.93, 95% confidence interval (CI): 1.12–3.33, P =.018] or rivaroxaban (aHR: 2.19, 95% CI: 1.26–3.79, P =.005) had significantly greater risk of major bleeding vs apixaban . Dabigatran initiation (aHR: 1.71, 95% CI: 0.94–3.10, P =.079) had a non‐significant major bleeding risk vs apixaban. When compared with warfarin, apixaban (aHR: 0.52, 95% CI: 0.30–0.89, P =.018) had significantly lower major bleeding risk. Patients initiating rivaroxaban (aHR: 1.13, 95% CI: 0.91–1.41, P =.262) or dabigatran (aHR: 0.88, 95% CI: 0.64–1.21, P =.446) had a non‐significant major bleeding risk vs warfarin. Conclusion: Among newly anticoagulated NVAF patients in the real‐world setting, initiation with rivaroxaban or warfarin was associated with a significantly greater risk of major bleeding compared with initiation on apixaban. When compared with warfarin, initiation with apixaban was associated with significantly lower risk of major bleeding. Additional observational studies are required to confirm these findings.